Integrating Technology with Academic Success by Evaluating ChatGPT’s Quality Compatibility and Impact on Student Performance - Irwansyah Suwahyu; Yohana Rara; Nur Syafitra Ramadhani; Rosidah; Putri Nirmala; Nurrahmah Agusnaya; Pramudya Asoka Syukur (Information Technology Education Journal, 2025)
The use of artificial intelligence (AI) technology in higher education has become an important element to improve students' academic performance. ChatGPT, as one of the generative AI applications, offers speed, ease of use, and relevant responses to support students' learning activities. This study aims to analyze the relationship between overall technology quality, technology characteristics, technology task suitability, compatibility, and performance impact in using ChatGPT on students' academic performance. This study used a quantitative approach with a cross-sectional design and purposive sampling technique involving 182 active student respondents using ChatGPT. Data were collected through an online questionnaire using a 5-point Likert scale covering five main variables. The results of descriptive analysis show a mean value that illustrates that students generally have a positive perception of the use of ChatGPT in supporting their academic activities. These findings suggest that ChatGPT has great potential in improving student productivity and comprehension, although service quality, task suitability, and function compatibility need to be continuously improved to better suit academic needs. Thus, the implementation of ChatGPT in higher education needs to be planned adaptively and ethically in order to optimally support students' learning success in the digital era